An investigation of pelvic floor muscle strength and vaginal resting pressure in nulliparous women of different race groups - Van der Walt, Ina (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScPhysio (Interdisciplinary Health Sciences. Physiotherapy))--University of Stellenbosch, 2010.